The Enforcement of Property Rights and Underdevelopment - Dabla-Norris, Era (IMF Working Papers; Working Paper ;, 1999)
This paper formalizes the role of legal infrastructure in economic development in a general equilibrium model with endogenously determined property rights enforcement. It illustrates the mutual importance of property rights protection and market production by the model's multiplicity of equilibria. In one equilibrium, property rights are enforced and market activity is unhampered. In the other, property rights are not enforced, which discourages economic activity and leaves the economy without the resources and incentives to enforce property rights. Even identically endowed economies may therefore find themselves in very different equilibria.